Workload Analysis in Determining the Optimal Number of Workers with The Work Load Analysis and Work Sampling Approach in Tofu MSMEs - Alghifari, Muhammad Reza; Rahdiana, Nana; Suryadi, Suryadi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
Workload is one of the things that greatly influences the product results in the tofu manufacturing industry of UMKM Tahu NR, which has 6 employees. At the beginning of the survey, it was indicated that there were problems experienced by UMKM in the implementation of tofu production, namely low employee work productivity, which resulted in delays in the completion of tofu production; consumer demand was also delayed due to the high workload experienced by the Operator. This study aimed to analyze the workload experienced by the UMKM Tahu NR Operator. This study applies the Work Load Analysis (WLA) and Work Sampling methods to determine the workload and the optimal number of workers. From the study results, the total excess workload of operators was 116%. One of the factors was due to a poor work environment, with an atmospheric level of 7 points in the ILO table, from the results of dividing the total workload and the total number of operators, the optimal number of workers for UMKM Tahu NR was 8 production operators with a workload of 87%. Keywords: Work Load, Work Load Analysis, Work Sampling, Optimal Workforce, Employee Productivity